2019
DOI: 10.4236/jbise.2019.128030
|View full text |Cite
|
Sign up to set email alerts
|

Data Transmission Delay in Medtronic Reveal LINQ<sup>TM</sup> Implantable Cardiac Monitor: Clinical Experience in 520 Patients

Abstract: Background: The Implantable Cardiac Monitor (ICM) is an invaluable tool for detecting cardiac arrhythmias by providing physicians. Critical to the success of ICMs depends on how quickly and accurately the data can be transmitted to a physician's office after an arrhythmic event. Then, the clinical event can be analyzed and the treatment will be provided accordingly. However, no reports have been published as to how efficiently the ICM data is transmitted. Methods: There is a retrospective review of 520 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A similar data upload issue was noted with the ILR. The Reveal LINQ™ device can store EGM data for 27 min of patient-activated episodes and 30 min of automatic-detected episodes, 39 hence, if multiple episodes are recorded over this time period without being downloaded to the base device, data are overwritten.…”
Section: Discussionmentioning
confidence: 99%
“…A similar data upload issue was noted with the ILR. The Reveal LINQ™ device can store EGM data for 27 min of patient-activated episodes and 30 min of automatic-detected episodes, 39 hence, if multiple episodes are recorded over this time period without being downloaded to the base device, data are overwritten.…”
Section: Discussionmentioning
confidence: 99%
“…Chokesuwattanaskul and colleagues showed that 63% of the data transmission delay was due to the MyCareLink transceiver not being in close enough proximity to the device, whereas the remaining 37% was caused by connectivity issues between the transceiver and the network. 12 Muniyappa and colleagues found that only 31% of patients were completely adherent to remote monitoring. 13 This is especially significant, given that the level of adherence to remote monitoring correlates with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, transmission rates between the ICM and data management systems have been an issue in the past, 16 with reported transmission success <80% 17 . These delays have the potential to impact patient care as only 11.7% of identified life‐threatening events were transmitted from the Medtronic Reveal LINQ™ cardiac monitor within 24 h and 35.8% took longer than 10 days to be transmitted in a 2019 study 16 . Here, the Bluetooth interface between the LUX‐Dx and the LATITUDE Clarity system, via dedicated smartphones, has been excellent with daily transmissions occurring 86% of the time, and comparable to those achieved with handheld wands and bedside transmitters that report success rates, ranging from 79.5% for the Medtronic Reveal LINQ™ 17 and 92.2%, 18 93.8%, 19 and 94.9% 20 for the Biotronik BioMonitor 2.…”
Section: Discussionmentioning
confidence: 99%
“…This low rate of infection is consistent with other reports of low infection rates (0%-1.6%) [11][12][13][14][15] The device performance measures reported here affirm in vivo prior findings in an in silico environment. Likewise, transmission rates between the ICM and data management systems have been an issue in the past, 16 with reported transmission success <80%. 17 These delays have the potential to impact patient care as only 11.7% of identified life-threatening events were transmitted from the Medtronic Reveal LINQ™ cardiac monitor within 24 h and 35.8% took longer than 10 days to be transmitted in a 2019 study.…”
Section: Discussionmentioning
confidence: 99%